The Political Faces of Evangelicals in Recent Argentina (Revista Rupturas, 2018)
In this article we analyze the new political faces of evangelicals in recent Argentina focusing on their interventions in two public controversies: the extension of sexual and reproductive rights and the draft law of cults. Backed by the qualitative research that supported our doctoral thesis and in dialogue with the main background of the field, we will show that the deep divergence in the evangelical positions evidenced the breaking of its constitution as a social movement at the same time as its growing socio-political legitimation as an active religious minority in the public space. We will also identify the multiple alliances between evangelical and Catholic actors as one of the most important reconfigurations in the Argentine religious political field since the democratic recovery.
Keywords: Evangelical; Argentina; politics